2013
DOI: 10.1007/s11102-013-0544-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment satisfaction on quality of life of patients with acromegaly

Abstract: In acromegaly, quality of life, status of depression and satisfaction of the subjects with their treatment are intercorrelated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 22 publications
1
31
1
1
Order By: Relevance
“…According to published studies men had better quality of life in some studies [4,16,19], whereas others show opposite results [5,20,21]. In our study younger patients had slightly higher quality of life scores, but again, these failed to reach statistical significance.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…According to published studies men had better quality of life in some studies [4,16,19], whereas others show opposite results [5,20,21]. In our study younger patients had slightly higher quality of life scores, but again, these failed to reach statistical significance.…”
Section: Resultscontrasting
confidence: 69%
“…In our study younger patients had slightly higher quality of life scores, but again, these failed to reach statistical significance. Previous studies showed that younger age was associated with better quality of life [14] and negative influence of age has been reported [5], whereas other studies have found no relationship [4,16,21,22]. In a recent Japanese study young age and previous radiotherapy were found to be associated with lower quality of life [23].…”
Section: Resultsmentioning
confidence: 94%
“…Generally, achieving a biochemically-controlled status only by surgery is superior to the continuous pharmaceutical therapy required for this status. Furthermore, the economic burden and inconvenience of pharmaceutical therapy could be of concern to patients with acromegaly [28]. We speculate that these disadvantages could deteriorate the comprehensive QoL in patients receiving pharmaceutical therapy, even if their physical condition is not impaired in a biochemically-controlled status.…”
Section: Discussionmentioning
confidence: 98%
“…One possibility to explain these results is that the burden of disease could indirectly impair QoL. Indeed, illness perception and treatment satisfaction are associated with QoL in patients with acromegaly [28,29]. Such factors could affect the psychological condition indirectly but perhaps affect not only the appearance score.…”
Section: Discussionmentioning
confidence: 99%
“…Webb et al (8) developed the AcroQoL using literature searches, interviews with expert endocrinologists and patients, and exploratory statistical methods, and they found the measure to contain a threesubscale, a two-subscale, and a single total score scoring method. At present, many studies have measured QoL and changes in QoL predominantly using the single total score of the AcroQoL (9,10,11). However, the World Health Organization (WHO) has recommended that QoL be treated as a multidimensional construct that, at a minimum, contains physical, psychological, and social aspects of QoL (12).…”
Section: Introductionmentioning
confidence: 99%